Educational Inspectorate and European Educational Cooperation Programmes: Insights and Lessons from Professional Practice - Moreno Fernández, Encarnación (Avances en Supervisión Educativa, 2026)
European educational cooperation programs have contributed to broadening the international dimension of education systems by promoting mobility, institutional cooperation, pedagogical innovation, inclusion and mutual learning among countries. This article offers a systematized professional reflection on participation in different European projects, first from the perspective of teaching and later from that of educational inspection. Drawing on experiences linked to programs such as Socrates, Comenius, Comenius Regio and Erasmus+, the article analyses the opportunities these initiatives provide for school improvement, teachers’ professional development, the exchange of good practices and the comparison of European educational models. Particular attention is paid to the role that educational inspection can play in promoting, supporting, monitoring, evaluating and institutionally coordinating these initiatives. The experience analyzed shows that the involvement of educational inspection in European projects helps connect educational policies with school practice, strengthens cooperation among administrations and educational institutions, and promotes a professional culture oriented towards quality, equity, inclusion and continuous improvement. The article concludes that educational inspection should not remain outside the European dimension of education but should take part in it as an agent of supervision, guidance, coordination and institutional improvement.